An Examination Of The Variables Impacting The Final Results Of Entrepreneurship Instruction For Learners As Individuals And Working Groups - Qingling, Wang; Paramalingam, Muhantha (Journal of Neonatal Surgery, 2025)
This research seeks to understand the factors that influence the results of entrepreneurship courses by examining the students and their teams. Since this discipline is becoming more relevant in producing future corporate leaders, it is crucial to study what influences the efficacy of entrepreneurship education to improve teaching methods. Businesses, instructors, and students were all polled in this study to get at its measurable results. Inspiration, group dynamics, pedagogical approaches, and background in the corporate world are some of the key areas covered. The research found that students' academic performance might be improved with the use of individualized learning plans, prior knowledge of entrepreneurial principles, and intrinsic drive. The effectiveness of entrepreneurial endeavours is heavily influenced by elements such as team cohesiveness, talent variety, and collaborative approaches, according to research on team-based learning. A study that examined the effects of mentoring and experiential learning on both group and individual productivity is part of the research. Some research suggests that tailored interventions, such as focused skill development and individual feedback, may improve the effectiveness of entrepreneurship programs. The results of this research may be useful for educators in the field of entrepreneurship education since they shed light on the many aspects that influence students' development and, therefore, might lead to the development of more efficient curriculum. Schools may be able to help students and teams flourish in the entrepreneurial sphere if they focus on these characteristics